Effectiveness of frenectomy for ankyloglossia correction in terms of breastfeeding and maternal outcomes: A critically appraised topic. Issue 1 (3rd April 2019) - Butenko, Hannah; Fung, Vanessa; White, Sarahlouise
ABSTRACT: A critically appraised topic (CAT) is one form of rapid review that can be particularly useful for informing practice (White, Raghavendra, & McAllister, 2017). The purpose of this CAT was to determine whether lingual frenectomy is effective in improving breastfeeding outcomes (compared with no surgical intervention) in infants with tongue tie under the age of 4 months. The effectiveness of lingual frenectomy (frenotomy) in improving breastfeeding outcomes was considered through the critical appraisal of three systematic reviews. In addition to the methodology, the authors present and discuss the findings of this CAT. The authors propose an update to this CAT in January 2021.